The Effect of Using Card Media on Students Speaking Skills at Senior High School of Muhammadiyah Gadingrejo - Alfi Khoirun Nisa; Fitri Wulandari; Defrilia Ramades; Ahyatun Nadhofa; Adelia Intan Fatimah (English Teaching and Linguistics Journal (ETLiJ), 2023)
Media is one important component that can be used by teachers to teach. In teaching English, the media is known as a tool to assist teachers in delivering material to students. Using media in teaching engages students and can help motivate students to learn. This study used quantitative research with a one-group pretest-posttest design. The population is all students of Senior High School of Muhammadiyah Gadingrejo and the sample is 16 people. Data were taken from test results and analyzed with quantitative data using data collection procedures in the pre-test (written test), treatment (learning) using Card media and post-test (written test). The test given is a written test in the form of multiple choices related to the theme to be presented, namely about congratulation and complement. on the initial test (pre-test) to get an average of 55.63, then given treatment in the form of delivering material using Card media and practicing dialogue on the material that has been delivered and getting the results of the final test (post-test) with an average of 70.12. so that it increased by14.49. Therefore, it can be concluded that the use card media which is applied in learning can affect students' speaking abilities. The results of this study indicate that card media can be applied in the teaching and learning process, especially in improving the speaking skills of Senior High School students of Muhammadiyah Gadingrejo.